Targeted metabolomics unravels the mechanism by phenylpropanoid-rich of the peel of Zea mays L. ameliorates metabolic disorders in diabetic mice through gut microbiota modulation - Cheng, Xiaotian; He, Jinyan; Yang, Yuru; He, Yaonan; Chen, Guangtong; Ling, Bai; Wang, Andong (Frontiers in Pharmacology, 2025)
BackgroundDiabetes is one common clinical symptoms of metabolic disorders. The peel of Zea mays L. is a folk remedy for diabetes that has not been thoroughly studied. The effects and mechanisms on diabetes complicated glucose and lipid metabolism disorders are still unknown now.PurposeThe research is intended to elucidate the constituent of phenylpropanoid enriched of Zea mays L. (YMP), and investigate the treatment and mechanism on amending glucose and lipid metabolism disorders.MethodsThe constituents of YMP were systematacially identified by HPLC-Q-TOF-MS/MS and NMR. To assess the effects of varying YMP doses, diabetic mice induced by streptozotocin and a high-fat diet were divided into groups. Targeted serum metabolomics investigations were conducted using UHPLC-LTQ-Orbitrap MS. Moreover, 16S rRNA analysis was employed to elucidate the intricate mechanisms through the gut microbiota modulates lipid and glucose metabolism.ResultsIt demonstrated that the primary component of YMP was luteolin. At a high dosage of 160 mg/kg/day, YMP considerably reduced the values of the oral glucose tolerance test, insulin, and blood glucose (p < 0.001). After administration, insulin resistance indexes decreased. YMP reversed the accumulation of glycogen in the liver and reduced hepatic lipid deposition. Compared to MOD group, the concentration of luteolin is higher and its metabolite, indicating that luteolin may be adequately absorbed and have an influence on the circulatory system. The results of 16S rRNA sequencing demonstrated that YMP and gut microbiota interacted to positively regulate beneficial bacteria such as Bifidobacterium, Ligilactobacillus, and Lactobacillus.ConclusionThis work investigated the regulating effect of YMP on the liver glycolipid metabolism for the first time, and it also showed the underlying mechanism through gut microbiota. According to these studies, YMP has a lot of potential to be used as a supplemental treatment for complex metabolic illnesses like diabetes. It offered empirical support for the use of alternative medicine in the area to treat complex problems of glucose and lipid metabolism in diabetes.